Heat transfer evaluation of industrial pneumatic cylinders - J. F. Carneiro (2007)
Automatic positioning devices are worldwide used in tasks like handling or assembly, making them key components of modern manufacturing systems. Pneumatic solutions are usually less expensive than their electrical counterparts, are more reliable and require less maintenance. However, the complex nonlinear nature and high model order of pneumatic systems lead to a very difficult control task. These problems make model order reductions and simplifications a common practice in servo pneumatics. The heat transfer between air inside the cylinder and its environment is usually neglected or only indirectly accounted, since it varies with pressure, temperature and speed of the actuator, which makes its experimental assessment difficult. In this work we present a simple yet accurate procedure, based on a thermal time constant, enabling its evaluation. The procedure is validated by simulation studies and furthermore the heat conductance of three industrial actuators is experimentally determined.